Fuzzy-Based Fitness–Distance Balance Snow Ablation Optimizer Algorithm for Optimal Generation Planning in Power Systems - Demirbas, Muhammet; Duman, Serhat; Ozkaya, Burcin; Balci, Yunus; Ersoy, Deniz; Döşoğlu, M. Kenan; Guvenc, Ugur; Altun, Bekir Emre; Uzel, Hasan; Kaymaz, Enes (MDPI AG, 2025)
Economic dispatch (ED) is one of the most important problems in terms of energy planning, management, and operation in power systems. This study presents a snow ablation optimizer (SAO) algorithm developed with the fuzzy-based fitness–distance balance (FFDB) method for solving ED problems in small-, medium- and large-scale electric power systems and determining the optimal operating values of fossil fuel thermal generation units. The FFDB-based SAO algorithm (FFDBSAO) controls early convergence problems through balancing exploration–exploitation and improves the solving of high-dimensional optimization problems. In the light of extensive experimental studies conducted on CEC2020, CEC2022, and classical benchmark test functions, the FFDBSAO2 algorithm has shown superior performance against its competitors. Wilcoxon and Friedman’s statistical analysis results confirm the performance and efficiency of the algorithm. Moreover, the proposed algorithm significantly reduces total fuel cost by optimizing fossil fuel thermal generation units. According to the results, the scalability and robustness of the algorithm make it a valuable tool for solving large-scale optimization problems in the planning of electric power systems.
Keywords: fuzzy fitness–distance balance method; Technology; power system planning; T; economic dispatch; optimization; snow ablation optimizer